Intensity and Prevalence Trichodina sp. on Tilapia Fish Seeds (Oreochromis niloticus) at the Jatiwangi Cultivation Pond, Majalengka - Erna Nurhasanah; Mulyani, Yuniar; Zidni, Irfan; Grandiosa, Roffi (Universitas Islam Lamongan, 2025)
The aim of this research is to determine the intensity and prevalence values ​​of Trichodina sp., using the scrapping method. Time and location of research from May to June 2024 at the Aquaculture Laboratory of the Faculty of Fisheries and Marine Sciences, Universitas Padjadjaran and the Parasitology Laboratory at the Cirebon Marine and Fishery Products Quality Control and Supervision Agency (BPPMHKP). Exploratory-descriptive research method. Morphological identification using random sampling is identified microscopically. The results of the research obtained an intensity value of 31.8 individuals/head. Meanwhile, the prevalence value was 79.16%. There are 5 species of Trichodina sp. found were Trichodina acuta, Trichodina heterodentata, Trichodina nobilis, Trichodina reticulata, and Trichodina nigra.